A TEM in situ study of the softening of Tungsten by Rhenium. (1st August 2020) - Caillard, Dr. Daniel
Abstract: Transmission electron microscopy in situ straining experiments have been carried out in a W–8% Re alloy, between 100 K and 300 K, in order to determine the origin of softening by alloying with Re. The geometry and kinetics of glide show that Re solutes do not induce any change of main slip plane. The only clearly visible effect of Re is the pinning of screw dislocations at super-jogs, which should a priori induce some hardening, but which in fact has only a weak effect. Local measurements of the applied shear stress at the scale of individual dislocations nevertheless confirm that softening is well reproduced in the micro-samples. It is thus concluded that softening results from a decrease of the strength of Peierls valleys with respect to pure W. Graphical abstract: Image, graphical abstract